State of the art review on mix design and mechanical properties of warm mix asphalt. Issue 7 (3rd October 2019) - Shiva Kumar, G.; Suresha, S.N.
Abstract : Warm mix asphalt (WMA) is a high-speed emerging technology of producing asphalt mixture at lower temperature with equivalent performance of hot mix asphalt (HMA). It offers benefits such as energy savings, compaction aid for stiffer mixes, reduces emission, and reduces asphalt binder aging during production. This paper is an overview of mix design concept, mix design properties and mechanical properties (moisture-induced damage, rutting resistance and fatigue life) of WMA and same was compared with the properties of control HMA mixtures. Review indicates that mix design concept of WMA is similar to that of control HMA and possesses better mix design properties. Regarding mechanical properties, WMA mixtures were found more prone to moisture-induced damage, rutting and fatigue than control HMA mixtures due to lower production temperature but similar or better resistance were noticed with the use of modified and higher grade binders, addition of anti-stripping agents (ASA) and hydrated lime (HL), use of open graded mix and inclusion of recycled asphalt pavement (RAP). Further, the effect of nominal maximum aggregate size (NMAS) and design gyration (Ndesign ) on mix design, NMAS and aggregate type and its water absorption on moisture-induced damage, NMAS, wheel load, test temperature, air voids, and binder grade on rutting, and NMAS, air voids, and stress or strain levels on fatigue properties of asphalt mixtures were analysed. Results indicated that NMAS had the significant effect on moisture-induced damage, rutting resistance and fatigue life of WMA mixtures. WMA mixtures made with aggregates of higher water absorption values were more prone to moisture-induced damage and even fail to meet minimum (tensile strength ratio) TSR requirements. Results also indicated that WMA mixtures made with modified and higher grade binder grade were high rut resistant. WMA mixtures tested at high stress or strain levels shows higher fatigue damage compared to WMA mixtures tested at lower stress or strain levels.